Fine-tuning the assemblies of carbon nanodots and porphyrins. Issue 82 (1st October 2018) - Scharl, Tobias; Cadranel, Alejandro; Haines, Philipp; Strauss, Volker; Bernhardt, Sarah; Vela, Sonia; Atienza, Carmen; Gröhn, Franziska; Martín, Nazario; Guldi, Dirk M.
Abstract : We present charge-transfer assemblies of electron accepting, pressure-synthesized carbon nanodots (pCND s) and an electron donating porphyrin. Abstract : We present charge-transfer assemblies of electron accepting, pressure-synthesized carbon nanodots (pCND s) and an electron donating porphyrin. Amidine derivatization of the porphyrin allows for hydrogen bonding interactions with the carboxyl groups on the surface ofpCND s, which drive the formation of the assembly. Upon photoexcitation, this electron donor–acceptor supramolecular construct features ultrafast charge separation, and subsequent charge recombination in 27 ps.